Integrative Biomarker Assessment of the Influence of Saxitoxin on Marine Bivalves: A Comparative Study of the Two Bivalve Species Oysters, Crassostrea gigas, and Scallops, Chlamys farreri - Cao, Ruiwen; Wang, Dan; Wei, Qianyu; Wang, Qing; Yang, Dinglong; Liu, Hui; Dong, Zhijun; Zhang, Xiaoli; Zhang, Qianqian; Zhao, Jianmin (Frontiers in Physiology, 2018)
Harmful algae blooms have expanded greatly in recent decades, and their secreted toxins pose a severe threat to human health and marine ecosystems. Saxitoxin (STX) is a main paralytic shellfish poison naturally produced by marine microalgae of the genus Alexandrium. Despite numerous studies have assessed the impacts of STX on marine bivalves, comparative in vivo study on the toxicity of STX on bivalves with distinct accumulation ability (such as oysters and scallops) has been seldom investigated. The aim of this study was to identify whether distinct sensitivity exists between oysters, Crassostrea gigas, and scallops, Chlamys farreri under the same amount of STX exposure using multiple biomarker responses. The responses of different biochemical markers including oxidative stress markers [Catalase (CAT), superoxide dismutase (SOD), glutathione transferase (GST) and lipid peroxidation (LPO)] and immunotoxicity biomarkers [hemocyte phagocytosis rate, reactive oxidative species (ROS) production and DNA damages] were evaluated in bivalves after 12 h, 48 h and 96 h of exposure to STX. The integrated biomarker responses (IBR) value combined with two-way ANOVA analysis suggested that STX posed slightly severer stress on scallops than oysters for the extended period of time. This study provided preliminary results on the usefulness of a multi-biomarker approach to assess the toxicity associated with STX exposure in marine bivalves.